THE EFFECT OF COUNSELING USING LEAFLETS ON KNOWLEDGE AND ATTITUDE OF PARTNERSHIP MOTHERS ABOUT EXCLUSIVE BREASTFEEDING AT THE PRATAMA FRANS CLINIC - Srilina Br Pinem; Kamelia Sinaga; Imran Surbakti; Halmah Julianti (International Journal of Midwifery Research, 2022)
Exclusive breastfeeding can reduce infant mortality. Exclusive breastfeeding means no food or drink other than breast milk is given. S. This study aims to determine the effect of counseling using leaflets on the knowledge and attitudes of postpartum mothers about exclusive breastfeeding at the Frans Pratama Clinic in 2021. Held at the Frans Pratama Clinic in 2021. The sample in this study was all postpartum mothers at the Frans Pratama Clinic in 2021. The sampling method in this study was using a total sampling technique. The instrument used was a questionnaire (Questionnaire).